Ineffectiveness of Tigecycline against Persistent Borrelia burgdorferi - Barthold, Stephen W. (American Society for Microbiology (ASM), 2010)
The effectiveness of a new first-in-class antibiotic, tigecycline (glycylcycline), was evaluated during the early dissemination (1 week), early immune (3 weeks), or late persistent (4 months) phases of Borrelia burgdorferi infection in C3H mice. Mice were treated with high or low doses of tigecycline, saline (negative-effect controls), or a previously published regimen of ceftriaxone (positive-effect controls). Infection status was assessed at 3 months after treatment by culture, quantitative ospA real-time PCR, and subcutaneous transplantation of joint and heart tissue into SCID mice. Tissues from all saline-treated mice were culture and ospA PCR positive, tissues from all antibiotic-treated mice were culture negative, and some of the tissues from most of the mice treated with antibiotics were ospA PCR positive, although the DNA marker load was markedly decreased compared to that in saline-treated mice. Antibiotic treatment during the early stage of infection appeared to be more effective than treatment that began during later stages of infection. The viability of noncultivable spirochetes in antibiotic-treated mice (demonstrable by PCR) was confirmed by transplantation of tissue allografts from treated mice into SCID mice, with dissemination of spirochetal DNA to multiple recipient tissues, and by xenodiagnosis, including acquisition by ticks, transmission by ticks to SCID mice, and survival through molting into nymphs and then into adults. Furthermore, PCR-positive heart base tissue from antibiotic-treated mice revealed RNA transcription of several B. burgdorferi genes. These results extended previous studies with ceftriaxone, indicating that antibiotic treatment is unable to clear persisting spirochetes, which remain viable and infectious, but are nondividing or slowly dividing.